Agile project management practises for digital production - Andersson, Fred; Sandahl, Elin (My University, 2021)
Project management is constantly evolving to be able to adapt to the circumstances needed to complete the steps during a project. When there is a increased demand for exibility and customer collaboration, new concepts are implemented. One example of this is the software development industry. In this industry it is common for customers to not have requirements set in stone at the beginning. Instead they have a general picture that can be built upon and completed in several iterations. From these conditions agile project management evolved as a symbiotic way of working with stakeholders. There are other industries that also have been affected by the increased speed and cooperation between companies and customers. One of these are digital visual production. This industry works both with technical and artistic aspects of producing digital photo-realistic images used in commercial and promotional purposes. Just like software development, digital visual production often differ in project length, how well de fined the requirements are and the need to continually produce value for the customer. They are also both in need of being able to do rapid changes in some part of their produced software or visual material if it does not ful ll the intended goals. With these similarities in mind it could be a great opportunity to nd out if the agile practises could be used in not only software development but also in digital visual production. To answer if this is the case an interview study had been conducted at Rapid Images, a company working with producing digital imagery. There a team of people with different roles and expertise's have been interviewed to nd out if the conditions are similar enough to apply agile practises in a new field of work. Using the collected empirical data and theory of agile practises and principles results have been produced and conclusions drawn regarding the main pillars of agile practises. These are the following. Sprints can be used to divide the work in to realistic increments and continually produce. Daily stand up is a good concept if it is kept short and concise. Planning is important for monitoring progress and involve the team giving them ownership of the process. Retrospectives is a chance to reflect and improve processes. It is however important that action is taken on the suggestions during retrospectives. Cross functionality makes the team more exible but stands in conflict with excellence in speci c areas. Therefore it can be bene cfial to first master some areas of work before working with a wide range of tasks.
Keywords: agile; project; digital visual production; sprint; stand-up; planning; retrospectives; cross-functional teams